Koordinasi Dewan Perwakilan Daerah dengan Dewan Perwakilan Rakyat dalam Penyerapan Aspirasi Masyarakat (Studi Tentang Koordinasi Perencanaan dan Pembuatan Kebijakan Penyaluran Aspirasi Masyarakat) - Sri Sundari (Institut Ilmu Sosial dan Manajemen STIAMI, 2018)
Ideally, the Regional Representative Council/ DPR should receive the aspirations of the local community and then continue to receive the aspirations to the House of Representatives for consideration in drafting legislation or formulating state policies. However, the reality shows that the aspiration uptake by members of the Regional Representative Council conducted against the constituents in each region, has not been effectively coordinated in accordance with expectations. There has not been an effective coordination yet in receiving aspiration that indicates conflicts of interest between DPR and DPD.The purpose of this research is about the coordination between the DPD and the Parliament in providing services for the absorption of people's aspirations to be conveyed to the state institutions that pay attention to and heed the aspirations of the people; and take those aspirations as input in the discussion of draft laws and regulations.The research method used descriptive qualitative research approach. The informants of this research are the people who really know about the coordination process of DPD with DPR in absorption of community aspiration. Technique of collecting data based on literature study, interview, and observation.The results of the study show that coordination between DPD and DPR includes direct individual coordination, coordination of planning and policy making and ongoing coordination. Ongoing coordination that includes policy coordination and technical coordination of community aspiration absorption necessary to institutionalize coordination pattern of community aspiration absorption among DPD and DPR is still unclear; and so far there has been no pattern of coordination of effective absorption of community aspirations between DPD and DPR.